High-Power Ultrasound in Gas Phase: Effects on the Bioactive Compounds Release from Red Bell Pepper during In Vitro Gastrointestinal Digestion - Cristina Reche; Carmen Rosselló; Valeria Eim; Alberto Edel León; Susana Simal (MDPI AG, 2023)
High-power ultrasound in gas-phase (28.8 kW/m3 for 120 min at 17.5 ± 0.3 °C) has been evaluated as a pre-treatment to enhance the release of antioxidants and phenolic compounds from red bell pepper during digestion. The moisture content decreased (34 ± 4%) while both the antioxidant activity (between 4 ± 1% and 21 ± 1%) and the phenolic compounds content (37 ± 4%) increased after the treatment. Moreover, microstructural changes were observed in the treated sample, with the appearance of breaks in the plant tissue, cell shrinkage, and an increased number of cells per area unit (28 ± 2%). Bioaccessibility was determined by in vitro gastrointestinal digestion. The total release of antioxidants and phenolic compounds after gastrointestinal digestion was 22-55% higher and 45 ± 7% higher, respectively, in the sonicated sample, with cell swelling and a 9.2 ± 0.1% higher number of cells per area unit. Therefore, the ultrasound treatment caused microstructural changes in the red bell pepper tissue, which could help to explain the higher release of bioactive compounds.